التفسير المقارن للفظ ﴿‌ٱلۡفُرۡقَانَۗ﴾ في قوله تعالى: وَأَنزَلَ ‌ٱلۡفُرۡقَانَۗ: The Comparative Interpretation of the Word “al-Furqan” (the Criterion) in the Verse “and He Sent Down the Criterion” - Aya Fekry Abdelaziz; Mohamed Abdelaatif Abde-laati (Maʿālim al-Qurʾān wa al-Sunnah, 2024)
This study investigates the meaning of the Qur’ānic term “al-Furqān” as it appears in verse 4 of Sūrah Āl ʿImrān. It seeks to answer the core question: How should “al-Furqān” be understood in the phrase “wa anzala al-furqān” (and He sent down the Criterion)? By examining and categorising the interpretations of both early and contemporary Qur’anic exegetes, the study clarifies their approaches according to distinct exegetical methodologies. It then identifies the interpretation most consistent with established principles and evidence. Methodologically, the research employs the inductive approach to collect various interpretations, the analytical approach to examine these positions, and the comparative approach to weigh their merits against one another. The analysis reveals fourteen possible understandings of “al-Furqān.” Of these, six are considered unlikely, while eight are interpreted as complementary rather than contradictory meanings. The study concludes that the term “al-Furqān” is best understood as encompassing this broader spectrum of meanings, rather than being confined to one narrow definition. This integrative perspective is supported by contextual analysis of the verse and by exegetical insights, including comprehensive phrases offered by some scholars that reflect the term’s multifaceted significance. In light of these findings, the study recommends further application of comparative interpretive methodologies to investigate other Qur’anic terms and phrases with disputed meanings, thereby fostering a more nuanced understanding of the divine intent.